Role of Legislation and State Policy in Minimizing the Impact of Threats to Environmental Safety in the Automobile Transport Sector - I. V. Bryhadyr; I. V. Panova (Bulletin of Kharkiv National University of Internal Affairs)
The role of legislation and state policy in minimizing the impact of threats to environmental safety in the field of automobile transport has been studied. The main directions of the development of state policy and legislation in the field of reducing the negative impact of motor vehicles on the environment and public health have been defined.